2009
DOI: 10.1292/jvms.71.811
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Time between Removal and Cooling of the Canine Epididymis on Post-Thaw Caudal Epididymal Sperm Quality

Abstract: ABSTRACT. The effects of the time period between canine epididymis removal and cooling on post-thaw caudal epididymal sperm quality were investigated. Sperm recovered from the epididymis stored for 6 hr at 4 or 20C exhibited similar motility. However, when the epididymis was stored for 12 hr or longer at 20C, sperm motility was significantly lower than that at 4C (p<0.01). The post-thawed qualities of sperm recovered from the caudal epididymides that had been stored at 20C for 0 or 6 hr and then at 4C for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 14 publications
3
16
0
2
Order By: Relevance
“…Furthermore, the PF collected from the specific male dog did not worsen or improve the results in this study, likewise previously reported (Hori et al., ; Hori, Hagiuda, Endo, et al., ; Hori, Hagiuda, Kawakami, et al. ; Hori et al., ; Hori et al., ), and the difference between the PF used was not seen. Therefore, it seemed that there was not the influence with the different canine PF.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the PF collected from the specific male dog did not worsen or improve the results in this study, likewise previously reported (Hori et al., ; Hori, Hagiuda, Endo, et al., ; Hori, Hagiuda, Kawakami, et al. ; Hori et al., ; Hori et al., ), and the difference between the PF used was not seen. Therefore, it seemed that there was not the influence with the different canine PF.…”
Section: Discussionsupporting
confidence: 90%
“…the birth of offspring with a low conception rate [1][2][3]. The effects of cryopreservation on motility, as well as membrane and acrosomal integrity of canine epididymal spermatozoa have been previously investigated [4][5][6], but no information is available on its potential effect on DNA integrity. Sperm DNA integrity has been evaluated in fresh ejaculated [7][8][9][10] and epididymal canine semen [11].…”
Section: Introductionmentioning
confidence: 99%
“…These authors suggested that this higher value might have been due to the cold shock caused by the crushed ice that was used to transport the epididymis. However, for dog [22], stallion [23], and ram semen [24], it has been reported that the preservation of the epididymis at 4 C does not significantly alter the morphologic features of the spermatozoa it contains. A higher percentages of proximal droplets in spermatozoa collected via EE compared with samples collected via TRM from 18-month-old Angus bulls have also been reported [12].…”
Section: Discussionmentioning
confidence: 98%